Economics : a student's guide - Beardshaw, John.; Brewster, David; Cormack, Paul; Ross, Andrew (New York : Pearson Education, 1998)
A complete course in economics, suitable for A-Level, higher level cources, professional examinations and the first year degree students
Includes bibliographical references and index.
oif 20/02/15
Loan
Keywords: Economics